Integrating Local Culture into Early Literacy through Storybook Development for Children - Febiola, Anisa; Aryanti, Nurul; Heriani, Dian (EDUCAFL: Journal on Education of English as Foreign Language, 2025)
This study analyzes the ability of children's storybook writing, supported by cultural integration programs, to effectively promote local heritage preservation through early literacy. This study emphasizes the creation of a storybook titled "A Jumputan Miracle," which exemplifies the innovative integration of cultural aspects, traditional crafting methods, and narrative techniques to introduce young readers to the old art of Jumputan. This project employed a Research and Development (R&D) methodology, integrating requirements analysis, field research, and collaborative design to investigate the role of storytelling as an educational tool for enhancing cultural literacy and language acquisition. Illustrated narratives demonstrate the ability of storybooks to depict Palembang's unique traditions in an engaging and accessible way. Local artists and educators are prioritized for engagement to guarantee the authenticity of the content. This research highlights the substantial impact of storybooks on improving children's literacy and protecting intangible cultural heritage through the integration of creative storytelling and cultural preservation. This effort demonstrates the utilization of literature to preserve local customs and enhance early childhood education.